Does Green Governance Efficiency and Green Finance Polices Matters in Sustainable Environment: Implications for Public Health - Xu, Siyun; Zhu, Huiqin (Frontiers in Public Health, 2022)
Rapid and widespread changes in the environment and climate, such as rising temperatures, water and air pollution, floods, and droughts, disease vector migration are putting human health at risk. In this case, green governance is an essential driver for the restructuring of economic development and realizing a green technological revolution for sustainable development and its implications for public health. This article aims to explore the effects and interrelationships of green governance and green finance policies on sustainable development in various regions of China's from 2008 to 2018 using panel data estimation technique. The findings show that China's overall green governance index and green finance policies resulted in a substantial decrease in environmental pollution during the study time. Financial inclusion also be a factor to the reduction of CO2 emissions and has a positive influence on environmental security investment projects, according to our findings. China is on track to become a world leader in an enactment of green finance concept, and controllers must speed up the development of green finance products and strengthen financial institutions' ability to provide green credit. Policymakers should promote green governance and green fiancé to keenly play a part in environmental security projects that boost green spending while minimizing the procedural risk.